(untitled) (Comparative Professional Pedagogy, 2022)
The paper studies progressive experience of foreign language teachers’ education at leading universities of Great Britain (the University of Sheffield, London, Lancaster, Cambridge, Southampton, and Newcastle Universities) and the USA (the University of Illinois, New York University, Princeton and Yale Universities). It is defined that to get a qualification of a foreign language teacher in both countries one must obtain a degree in foreign language education or language teaching that can be provided by different programs in either Teaching/Education or Applied Linguistics for Language Teaching/ Second Language Acquisition (the title can somewhat differ depending on the university). It is found out that in the UK and US universities the latter focus on different aspects of language study such as morphology, syntax, semantics, psycholinguistics, and translation; bilingual education; and teaching foreign languages. Standards for the Preparation of Foreign Language Teachers in both countries are analyzed. Curricula, syllabi, compulsory and elective subjects, implementation of teaching practice and scientific research for foreign language teaching (FLT) are characterized. Comparative analysis of British and American education programs aimed at FLT is carried out. Similar features include combination of professional subjects (majors) and theoretical ones; development of skills to deliver lessons, develop lesson plans, and syllabi; provision of students’ exchange programs; wide use of multimedia technologies; adaptation to individual requirements and needs of students; prevalence of individual work of students in curriculum workload; interdisciplinary character of education; differentiation and focus on realization of students’ professional goals; flexibility and diversity of educational process; and inclusion of extra-curricular activities into the content of study. Different is the essence of education programs for FLT – in the USA they are more practice-oriented, whereas in GB students gradually switch from theory to practice. British curricula for FLT are more focused on language disciplines, whereas American ones are more concentrated on the development of sociocultural competence of students.